Governing the governors: A clinical study of central banks - Lars Frisell; Kasper Roszbach; Giancarlo Spagnolo (Sveriges Riksbank, 2008)
Recent research on central bank governance has focused mainly on their monetary policy task. As the sub-prime loan market turmoil reminded us - central banks play a crucial role in financial markets not only in setting monetary policy, but also in ensuring their soundness and stability. In this paper we study the specific corporate governance structures of a number of central banks in light of their complex role of inflation guardians, bankers' banks, financial industry regulators/supervisors and, in some cases, competition authorities and deposit insurance agencies. We review their current institutional arrangements, e.g. formal objectives, ownership, board and governor appointment rules, term limits and compensation, using both existing surveys and newly collected information; and we contrast them with the structures suggested in the corporate and public governance literatures, where present. Our analysis highlights a striking variety in central bank governance structures and a number of specific issues that appear unsatisfactorily addressed by existing research, including the incentive structure for governor and board members, the balance between central banks' multiple objectives, and the need for term limits or post-employment restrictions.
Keywords: G18; G34; G38; E58; 330; accountability; bank regulation; board structure; central bank independence; central banks; cooling-off periods; governance; governor remuneration; regulatory capture; term limits; Zentralbank; Zentralbankunabhängigkeit; Corporate Governance; Führungsorganisation; Welt